Tinjauan Penerapan Pembelajaran Berbasis Proyek (Project-Based Learning) Di Sekolah Menengah Atas (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
Project-based learning encourages students to develop collaboration, communication, problem solving, critical, and creativity skills. This model is widely used at the level of educational units such as junior secondary education and upper secondary education and even higher education. The aim of this research is to capture the research landscape related to Project-Based Learning in high school. The method used is bibliometric analysis. The data is obtained from the enhanced Scopus database. The results showed that the number of publications related to Project-Based Learning in high school increased every year from 2017 to 2022. The highest number of documents were in Indonesia and the United States, the highest number of documents were in institutions or universities in Indonesia. The research focuses are 1) Problem-Based Learning and Student; 2) Project-Based Learning, e-learning and STEM; 3) high school and inquiry based discovery learning.